Design of Tat Twam Asi-Discrepancy Evaluation Model Based on TOPSIS in Determining the Improvement Priority Aspect - Dewa Gede Hendra Divayana; Agus Adiarta; P. Wayan Arta Suyasa (Ital Publication, 2021)
This research aimed to provide information about the existence of the new evaluation model in the field of education. The intended evaluation model is called the Tat Twam Asi-Discrepancy evaluation model based on TOPSIS. This model serves to determine the dominant aspects become improvement priority, so later it can trigger the effectiveness of blended learning implementation. The method was used in this research was a development method using the Borg and Gall model, which only focused on the design development stage. Subjects were involved in the initial trials of the evaluation model design were four experts and 30 respondents to conducted simulation trials of TOPSIS calculation. The tools were used to conducted preliminary trials toward the evaluation model design and simulation trials of calculations were questionnaires. Analysis of the initial trial results toward the model design was done by comparing the quality percentage of the test results with the percentage of quality standards that refer to the eleven’s scale. Analysis of the simulation test results of the TOPSIScalculation was done by comparing the effectiveness percentage of the test results with the percentage of effectiveness standards that refer to the five’s scale. The results of this research indicate this evaluation model is highly qualified and effective is used to determine the most dominant evaluation aspect to become an improvement priority to realize the effectiveness of blended learning implementation. Doi: 10.28991/esj-2021-01285 Full Text: PDF